House prices, non-fundamental components and interstate spillovers: the Australian experience - Costello, Gregory; Fraser, Patricia; Groenewold, N. (Elsevier BV, North Holland, 2011)
Using Australian capital city data from 1984Q3–2008Q2, this paper utilizes a dynamic present valuemodel within a VAR framework to construct time series of house prices depicting what aggregate houseprices should be given expectations of future real disposable income – the ‘‘fundamental price” – andcontinues by comparing capital city fundamental prices with actual prices. The extent to which revealedcapital city ‘‘non-fundamental” components spillover from state to state, as well as their long-termimpact is also investigated. Results provide evidence of periods of sustained deviations of house pricesfrom values warranted by income for all state capitals with the greatest deviations arising in the NSWmarket and starting around 2000. In general NSW is relatively more susceptible to spillovers transmittedfrom other states while ACT and WA are most isolated from the rest of the country.